Use of a dual chamber pacemaker with a novel fallback algorithm as an effective treatment for sick sinus syndrome associated with transient supraventricular tachyarrhythmia. - Mayumi H; Uchida T; Shinozaki K; Matsui K (Pacing & Clinical Electrophysiology, 1993)
A dual chamber pacemaker having a fallback (FB) mode was utilized in nine patients with sick sinus syndrome (SSS) associated with transient supraventricular tachyarrhythmia (atrial fibrillation [Af] in three patients, atrial flutter [AF] in two, and paroxysmal atrial tachyarrhythmia [PAT] in four). Various degrees of abnormality of atrioventricular (AV) conduction were observed at the time of pacemaker implantation in five patients. In this pacemaker, a DDD mode was active during sinus rhythm, but the mode changed, through a given cycle of high rale tracking at an upper rate limit (URL), to VDI only during intrinsic atrial rate increases that were either normally or abnormally above the URL. The VDI mode automatically returned to DDD when the atrial rate fell below the URL. At follow-up periods of 7-12 months, this pacemaker appeared to be especially effective in those SSS patients with transient Af or AF. In the SSS patients with PAT, however, the FB mode was not active because the PAT rhythm was conducted to the ventricle without block (1:1 conduction) and thus the given cycles of ventricular tracking at the URL did not occur. From the repetitive FB starting tests that were performed during an Af period in one patient with transient Af, a 2:1 point setting of a given URL plus 30-50 ppm was required to quickly start the FB algorithm. Moreover, an atrial sensitivity setting that was less than half of the P wave amplitude was desirable. These results suggest that, when properly set, the DDD plus FB mode is useful in a SSS patient with transient supraventricular tachyarrhythmia when a significant degree of AV block is present.